A construct divided: prosocial behavior as helping, sharing, and comforting subtypes - Dunfield, Kristen A. (Frontiers in Psychology, 2014)
The development and maintenance of prosocial, other-oriented behaviors has been of considerable recent interest. Though it is clear that prosocial behaviors emerge early and play a uniquely important role in the social lives of humans, there is less consensus regarding the mechanisms that underlie and maintain these fundamental acts. The goal of this paper is to clarify inconsistencies in our understanding of the early emergence and development of prosocial behavior by proposing a taxonomy of prosocial behavior anchored in the social-cognitive constraints that underlie the ability to act on behalf of others. I will argue that within the general domain of prosocial behavior, other-oriented actions can be categorized into three distinct types (helping, sharing, and comforting) that reflect responses to three distinct negative states (instrumental need, unmet material desire, and emotional distress). In support of this proposal, I will demonstrate that the three varieties of prosocial behavior show unique ages of onset, uncorrelated patterns of production, and distinct patterns of individual differences. Importantly, by differentiating specific varieties of prosocial behavior within the general category, we can begin to explain inconsistencies in the past literature and provide a framework for directing future research into the ontogenetic origins of these essential social behaviors.